Molecular Cloning of a HMG-CoA Reductase Gene from Eucommia ulmoides Oliver. Issue 2 (22nd June 2006) - Jiang, Jihong; Kai, Guoyin; Cao, Xiaoying; Chen, Fengmei; He, Dongning; Liu, Qun
Abstract : The 3-hydroxy-3-methylglutaryl-CoA reductase (HMGR) catalyzes the conversion of HMG-CoA to mevalonate, which is the first committed step in the pathway for isoprenoid biosynthesis in plants. A full-length cDNA encoding HMGR (designated as EuHMGR, GenBank Accession No. AY796343) was isolated from Eucommia ulmoides by rapid amplification of cDNA ends (RACE). The full-length cDNA of EuHMGR comprises 2281 bp with a 1770-bp open reading frame (ORF) encoding a 590-amino-acid polypeptide with two trans-membrane domains revealed by bioinformatic analysis. Molecular modeling showed that EuHMGR is a new HMGR with a spatial structure similar to other plant HMGRs. The deduced protein has an isoelectric point (pI) of 6.89 and a calculated molecular weight of about 63 kDa. Sequence comparison analysis showed that EuHMGR had highest homology to HMGR from Hevea brasiliensis . As expected, phylogenetic tree analysis indicated that EuHMGR belongs to plant HMGR group. Tissue expression pattern analysis showed that EuHMGR is strongly expressed in the leaves and stems whereas it is only poorly expressed in the roots, which implies that EuHMGR may be a constitutively expressing gene. Functional complementation of EuHMGR in HMGR-deficient mutant yeast JRY2394 demonstrated that EuHMGR mediates the mevalonate biosynthesis in yeast.